Korean loanwords in Indonesian; A corpus-based study - Suhandano, Suhandano; Febrina, Ria; Isti'anah, Arina; Young, Hwang Who (UI Scholars Hub, 2024)
The borrowing of foreign lexicon in Indonesian is well documented. However, to date, research on Korean loanwords has remained unavailable. Against the backdrop of the Korean Wave (hallyu), this paper discusses the phonological adaptation of Korean loanwords in Indonesian and the way these loanwords contribute to the Indonesian lexical landscape. By collecting data on Korean culture from a selection of Instagram and Twitter (now X) accounts from the Indonesian community, our corpus shows that besides nouns, Korean loanwords also include adjectives and verbs. We identified 52 loanwords related to the domain of popular culture, including film, music, and food. The different phonological systems of Korean and Indonesian determine the assimilation processes in the Indonesian vocabulary. Since this paper involves big data stored in a corpus, it has the capacity to provide new insight in the ways Korean loanwords and their phonological structure are integrated in Indonesian and become linguistically acceptable.